Energy use patterns in German manufacturing from 2003 to 2017 - Kathrine von Graevenitz; Elisa Rottner (Journal of Economics and Statistics, 2023)
The manufacturing sector accounts for a substantial share of the German gross domestic product, employment and carbon emissions. Therefore, reducing its energy use and carbon emissions is of crucial importance to Germany's energy Transition. In this paper, we analyse energy use patterns in German manufacturing between 2003 and 2017, using rich administrative micro-data. We find that although the manufacturing sector has been faced with rising energy costs as a share of total costs, energy use has not declined except briefly during the economic crisis. We also find that energy intensity, and to a larger degree, carbon intensity follow a decreasing trend between 2003 and 2017. The stronger response of the latter variable can be attributed to changes in the fuel mix.
Keywords: D22; L60; Q41; 330; carbon emissions; energy intensity; energy use; fuel mix; manufacturing